It's time to swim! Zebrafish and the circadian clock - Vatine, Gad; Foulkes, Nicholas S. (FEBS letters, 2011)
The zebrafish represents a fascinating model for studying key aspects of the vertebrate circadian timing system. Easy access to early embryonic development has made this species ideal for investigating how the clock is first established during embryogenesis. In particular, the molecular basis for the functional development of the zebrafish pineal gland has received much attention. In addition to this dedicated clock and photoreceptor organ, and unlike the situation in mammals, the clocks in zebrafish peripheral tissues and even cell lines are entrainable by direct exposure to light thus providing unique insight into the function and evolution of the light input pathway. Finally, the small size, low maintenance costs and high fecundity of this fish together with the availability of genetic tools make this an attractive model for forward genetic analysis of the circadian clock. Here, we review the work that has established the zebrafish as a valuable clock model organism and highlight the key questions that will shape the future direction of research.